Political Interference in the Administration of Service Delivery in UMLALAZI Local Municipality of KwaZulu-Natal, South Africa - Mngomezulu, Sengiwakhile (Journal of Economics and Behavioral Studies, 2020)
South African political interference in the administration of service delivery is a serious problem in many municipalities, where municipalities are experiencing serious challenges in dealing with the interface between politicians and officials. Inappropriate political interference in administrative matters as well as strained relations between key political and administrative officials in the municipalities appear to be the order of the day. To understand the impact or consequences of political interference in the administration of service delivery, a case approach was adopted to evaluate the political interference in the administration of service delivery in uMlalazi Local Municipality of Kwazulu- Natal, South Africa. Participants comprises of Municipal Officials in the administrative side of the municipality, members of Ward Committee as well as other political parties expect the political party in power. The literature seeks to review the political-administrative interface, South African local government service delivery, conflation of legislative and executive roles of local government, reflection on local government performance and the critical issue of poor service delivery in South Africa.